Inhibition of MRGPRX2 but not FcεRI or MrgprB2-mediated mast cell degranulation by a small molecule inverse receptor agonist - Bawazir, Maram; Amponnawarat, Aetas; Hui, Yvonne; Oskeritzian, Carole A.; Ali, Hydar (Frontiers in Immunology, 2022)
Mas-related G protein-coupled receptor-X2 (MRGPRX2) expressed on mast cells (MCs) contributes to hypersensitivity reactions to cationic US-Food and Drug Administration (FDA) approved drugs such as the neuromuscular blocking agent, rocuronium. In addition, activation of MRGPRX2 by the neuropeptide substance P (SP) and the pro-adrenomedullin peptide (PAMP-12) is associated with a variety of cutaneous conditions such as neurogenic inflammation, pain, atopic dermatitis, urticaria, and itch. Thus, small molecules aimed at blocking MRGPRX2 constitute potential options for modulating IgE-independent MC-mediated disorders. Two inverse MRGPRX2 agonists, named C9 and C9-6, have recently been identified, which inhibit basal G protein activation and agonist-induced calcium mobilization in transfected HEK293 cells. Substance P serves as a balanced agonist for MRGPRX2 whereby it activates both G protein-mediated degranulation and β-arrestin-mediated receptor internalization. The purpose of this study was to determine if C9 blocks MRGPRX2’s G protein and β-arrestin-mediated signaling and to determine its specificity. We found that C9, but not its inactive analog C7, inhibited degranulation in RBL-2H3 cells stably expressing MRGPRX2 in response to SP, PAMP-12 and rocuronium with an IC50 value of ~300 nM. C9 also inhibited degranulation as measured by cell surface expression of CD63, CD107a and β-hexosaminidase release in LAD2 cells and human skin-derived MCs in response to SP but not the anaphylatoxin, C3a or FcεRI-aggregation. Furthermore, C9 inhibited β-arrestin recruitment and MRGPRX2 internalization in response to SP and PAMP-12. We found that a G protein-coupling defective missense MRGPRX2 variant (V282M) displays constitutive activity for β-arrestin recruitment, and that this response was significantly inhibited by C9. Rocuronium, SP and PAMP-12 caused degranulation in mouse peritoneal MCs and these responses were abolished in the absence of MrgprB2 or cells treated with pertussis toxin but C9 had no effect. These findings suggest that C9 could provide an important framework for developing novel therapeutic approaches for the treatment of IgE-independent MC-mediated drug hypersensitivity and cutaneous disorders.